2018
DOI: 10.1007/978-3-319-76732-1_11
|View full text |Cite
|
Sign up to set email alerts
|

A Squeezed Review on Coherent States and Nonclassicality for Non-Hermitian Systems with Minimal Length

Abstract: It was at the dawn of the historical developments of quantum mechanics when Schrödinger, Kennard and Darwin proposed an interesting type of Gaussian wave packets, which do not spread out while evolving in time. Originally, these wave packets are the prototypes of the renowned discovery, which are familiar as "coherent states" today. Coherent states are inevitable in the study of almost all areas of modern science, and the rate of progress of the subject is astonishing nowadays. Nonclassical states constitute o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 195 publications
(237 reference statements)
1
33
0
Order By: Relevance
“…Special properties are revealed in the Jaynes-Cummings model [299][300][301][302], and for dynamical systems ruled by either the su(1, 1) or the su(2) Lie algebras [257,[303][304][305][306][307][308][309][310]. The coherent states can be entangled [311][312][313][314], superposed [44][45][46][47]315], and constructed for non-Hermitian operators [86,87,316] in terms of either a bi-orthogonal basis [84,86,87,317] or noncommutative spaces [313,318,319], for which nonclassical properties can be found [87,107,320,321]. They have been also associated to super algebraic structures [314,[322][323][324][325][326], nonlinear oscillators [327][328][329], and solvable models…”
Section: Two Faces Of the Same Coinmentioning
confidence: 99%
“…Special properties are revealed in the Jaynes-Cummings model [299][300][301][302], and for dynamical systems ruled by either the su(1, 1) or the su(2) Lie algebras [257,[303][304][305][306][307][308][309][310]. The coherent states can be entangled [311][312][313][314], superposed [44][45][46][47]315], and constructed for non-Hermitian operators [86,87,316] in terms of either a bi-orthogonal basis [84,86,87,317] or noncommutative spaces [313,318,319], for which nonclassical properties can be found [87,107,320,321]. They have been also associated to super algebraic structures [314,[322][323][324][325][326], nonlinear oscillators [327][328][329], and solvable models…”
Section: Two Faces Of the Same Coinmentioning
confidence: 99%
“…In this article, we propose yet another alternative way to obtain a squeezed atom laser by using a model, which not only has a strong mathematical ground originating from the quantum group, but also it demonstrates ample interesting results in generating squeezed states and in other aspects of quantum optics [21][22][23][24][25]. Previously, it was shown that the optical squeezing properties are inherited in these models by construction, here we show that it is true for the atom laser case also.…”
Section: Squeezed Atom Laser For Bec With Minimal Lengthmentioning
confidence: 57%
“…However, unlike the usual nonlinear generalization, there are some interesting consequences that follow from such minimal length model. For instance, it has been shown that the squeezed states constructed out of these models are intrinsically more squeezed than the usual quantum optical models, for further details one may refer to a review article in the context [21]. Nevertheless, in order to apply these models in the construction of atom laser, let us discuss the associated mathematical detail briefly.…”
Section: Minimal Length and Generalised Uncertainty Principlementioning
confidence: 99%
“…In order to do that, we need the quantum state and eigen-energy spectrum of the deformed one dimensional simple harmonic oscillator. The perturbed Hamiltonian H (ml) of the deformed harmonic oscillator in noncommutative space is given by [2,72]…”
Section: Deformation With Minimal Lengthmentioning
confidence: 99%